Answer:
Multiply Equation (1) by -3
Step-by-step explanation:
The two equations are:
[tex]$ 5x - 2y = 17 \hspace{20mm} \hdots (1) $[/tex]
[tex]$ 3x + 7y = 43 \hspace{20mm} \hdots (2) $[/tex]
In the first step, Equation (1) is multiplied by -3.
i.e., -3(5x - 2y = 17) = - 15x + 6y = - 51
The next instruction is to multiply Equation (2) by 5.
i.e., 5(3x + 7y = 43) = 15x + 35y = 215
We add the two new equations in the next step, to eliminate the variable x.
The sum is 41y = 164
Dividing by 41 through out, we get:
y = 4
Now, we solve for x.
To do this substitute the value of y in Equation (1) or (2).
We will substitute in (1).
Therefore, we get: 5x - 2(4) = 17
⇒ 5x = 25
⇒ x = 5
Therefore, (x, y) = (5, 4) is the solution to the equations given.